2014
DOI: 10.1152/ajprenal.00344.2014
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase 2 deficiency leads to increased pyelonephritis susceptibility

Abstract: Carbonic anhydrase 2 deficiency leads to increased pyelonephritis susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 49 publications
0
34
0
Order By: Relevance
“…UPEC infection. Female IC and PC reporter mice were transurethrally inoculated with uropathogenic E. coli (UPEC strain CFT073) at a dose of 1 ϫ 10 8 colony forming units as described previously (13). One hour later, mice were killed, IC and PCs were flow sorted, and AMP mRNA was measured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…UPEC infection. Female IC and PC reporter mice were transurethrally inoculated with uropathogenic E. coli (UPEC strain CFT073) at a dose of 1 ϫ 10 8 colony forming units as described previously (13). One hour later, mice were killed, IC and PCs were flow sorted, and AMP mRNA was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Collecting ducts consist of two cell types: principal cells (PCs) that express aquaporin 2 (AQP2) and regulate water along with salt reabsorption and intercalated cells (ICs) that express vacuolar H ϩ -ATPase (V-ATPase, B1 subunit) and help maintain acid-base homeostasis (4,14). Increasing evidence indicates that ICs also function as important innate immune cells notably, 1) bacteria preferentially attach to the apical surface of ICs (5); 2) ICs express innate immune proteins (10,25,29,31); 3) mice deficient in ICs are more susceptible to bacteruria and pyelonephritis (13,25); and 4) renal ICs sense and mediate inflammation (3). Studies of the innate immune role of ICs and/or collecting ducts have mostly been limited to a single gene or protein (24, 29 -31).…”
Section: Introductionmentioning
confidence: 99%
“…27 Similarly, in a model of experimental pyelonephritis, we have shown that mice lacking carbonic anhydrase 2 develop an increased renal UPEC burden and decreased UPEC clearance independent of serum bicarbonate concentrations or urine pH. 37 Carbonic anhydrase 2 is a key enzyme responsible for the generation of the hydrogen gradient of the intercalated cell. This finding therefore suggests that the innate immune activity of the intercalated cell requires intact acid-base control mechanisms.…”
Section: Introductionmentioning
confidence: 90%
“…This finding therefore suggests that the innate immune activity of the intercalated cell requires intact acid-base control mechanisms. 37 Although the mechanisms responsible for the antimicrobial activity of the collecting duct are only beginning to be described, intercalated cells have been shown to produce innate immune proteins such as IL-18, bacteriostatic proteins such as iron siderophores, and potent bactericidal AMPs (Table 1). 14,27,38 Some of these antimicrobial proteins are produced at high basal levels to prevent bacterial attachment whereas others are rapidly induced to facilitate pathogen clearance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mice with intercalated celltargeted dysfunctions have increased risk of UTI with bacterial challenge. 75,76 Well-phenotyped cohorts of these conditions and genome-wide studies are needed to identify the entire milieu of the innate defense that may be targeted for novel therapeutics in preventing or treating UTIs.…”
Section: Resultsmentioning
confidence: 99%